miR-125b and miR-223 Contribute to Inflammation by Targeting the Key Molecules of NFκB Pathway - Valmiki, Swati (Front Med (Lausanne), 2020)
The contribution of miRNA in the pathogenesis of ulcerative colitis (UC) has emerged in the past few decades. Differential miRNA expression has been demonstrated in UC patients, and their ability to target the genes involved in inflammatory pathway has also been explored in recent years. miR-125b and miR-223 have been demonstrated to get upregulated within the colonic mucosa of UC patients. Here, we explored the biological relevance of miR-125b and miR-223 altered expression during UC by identifying the potential gene targets for miR-125b and miR-223. TRAF6 and A20, the signaling molecules involved in the NFκB pathway, were identified as target genes for miR-125b while IKKα was identified as a gene target for miR-223. The colonic mucosal samples from UC patients exhibited a significant rise in miR-125b and miR-223 expression while a subsequent downregulation was observed in the expression of TRAF6, A20, and IKKα. This negative correlation between miRNAs and their respective target genes was validated by co-transfecting miR-125b and miR-223 in HT29 cells. Co-transfection with miR-125b resulted in a marked decline in the expression of TRAF6 and A20, while the miR-223 co-transfected cells exhibited lower IKKα expression levels. Additionally, co-transfection with miR-125b or miR-223 in HT29 cells caused higher p65 and pro-inflammatory cytokines (IL-8 and IL-1β) expression upon LPS stimulation. From our findings, we highlight the possible contribution of miR-125b and miR-223 in regulating the inflammatory response during UC by negatively regulating the expression of TRAF6, A20, and IKKα. Therefore, we conclude that these two miRNAs could be considered as potential candidates for developing promising biomarkers for screening and diagnosis of UC.